Effect of magnetic stirring on AlFeSi intermetalics of an A356 aluminum alloy - Bustos,Óscar (2022)
ABSTRACT The effect of the application of forced convection during the continuous solidification of A356 aluminum alloy over microstructural parameters of AlFeSi phases has been presented in this work. The investigation has been made on the fact that as an alloy solidifies under the action of a rotating magnetic field; a non-dendritic casting structure will be obtained. The Al-Si alloy has been studied using magnetic stirring equipment with permanent magnets. This device has allowed the study of the rotational speed (degree of stirring) effect on the micro- and macro- solidification structure. Different analyses and tests have been carried out, such as micro- and macro-structural analysis. The results have shown that magnetic stirring affects the cooling curves, expanding the solidification range. Microstructural evolution of the alloys has also been observed, from a 100% dendritic structure to a mature rosette type structure, in addition to a notable grain size decrease, which may improve the material’s mechanical behavior. The results show that all the microstructural parameters of the AlFeSi phases (quantity, size, shape factor, particle area, and aspect ratio) decrease when stirring is applied to the alloy during its solidification.